Stereoselective Synthesis of Dioxolanes and Oxazolidines via a Desymmetrization Acetalization/Michael Cascade - Rubush, David M.; Rovis, Tomislav (Synlett, 2014)
The desymmetrization of p-quinols using a Brønsted acid catalyzed acetalization/Michael cascade was achieved in high yields and diastereoselectivities for aldehydes and imines. Use of a chiral Brønsted acid allowed for the synthesis of 1,3-dioxolane and 1,3-oxazolidine products in modest enantioselectivity.
Keywords: acetals; desymmetrization; Michael addition; stereoselective synthesis; cascade catalysis